Analysis of the 2007/8 Defra Farm Business Survey Energy Module - Williams, Adrian G.; Pearn, Kerry R.; Sandars, Daniel L.; Audsley, Eric; Parsons, David J.; Chatterton, Julia C. (Cranfield University, 2010)
Key points This study has delivered an invaluable baseline estimate of energy use and greenhouse gas (GHG) emissions on commercial farms in England. Energy use and GHG emissions associated with particular commodities were quantified and results broadly agreed with those derived by Life Cycle Assessment, but with much scatter in the environmental performance of farms.Direct energy use on farms was generally less that indirect (embedded) energy use, except for horticulture, which is dominated by heating fuel use. In contrast, most GHG emissions are incurred on farms, rather than as embedded emissions.Scatter in both environmental and economic performance underlies the somewhat disappointing finding of no clear positive link between farm financial performance and energy use or GHG emissions. However, the mere existence of these ranges shows that there is scope for improvement in both financial and environmental performance and that there is no apparent barrier for both to be achievable in harmony. The recording of such farm-level energy data is essential for the future, as it should enable improvements to be made in efficiency of energy use. The improved UK agricultural GHG inventory will depend on high quality energy data on agricultural activities. This study will be invaluable in identifying the level of detail needed. Future data requirements include: contractor work rates and fuel use per unit area and per unit time, fertiliser and pesticide use by brand name, enhanced output data, especially animal live weights, and horticultural produce recorded by weight rather than by value.